INTERNET INFLUENCE ON INTERNATIONAL POLITICS - E. S. Zinovieva (Vestnik MGIMO-Universiteta)
International and political aspects of the Internet development are analyzed in the article. The Internet is a key infrastructure of the emerging global information society. Based on the works by respected information society scholars, the effects of the Internet growth for international relations and world politics are generalized. Networked organization, transnational nature, accessibility and openness of the Internet contribute to the processes of globalization and trans-nationalization, increase international cooperation, and penetrability of state borders. Segmentation and marginalization of the societies is the response to the fast growth in the volumes of information available throughout the world. State borders, geographical divisions amplify new lines of divides in the information realm. Authoritarian states, such as China, Myanmar, Burma, Pakistan, filter information with the help of big internet companies, such as Yahoo and Google. Internet companies wish to gain access to the fast growing markets of these countries and thus are ready to provide authorities the confidential information of the users and block access to certain internet sites. Internet creates new divide between “information-wealthy” and “information-poor”, which is the source of the new contradiction on the international arena. New forms of international conflicts, including information war, network wars, hacker attacks etc. are one of the negative results of the fast internet and information technologies development.At the same time development of information technology poses new challenges to international and national security, which can only be reduced through collective efforts of the international community.